2020
DOI: 10.3390/axioms9010034
|View full text |Cite
|
Sign up to set email alerts
|

On Grothendieck Sets

Abstract: We call a subset M of an algebra of sets A a Grothendieck set for the Banach space b a ( A ) of bounded finitely additive scalar-valued measures on A equipped with the variation norm if each sequence μ n n = 1 ∞ in b a ( A ) which is pointwise convergent on M is weakly convergent in b a ( A ) , i.e., if there is μ ∈ b a A such that μ n A → μ A for every A ∈ M then μ n → μ weakly in b a ( A ) . A subset… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…It is observed that the Grothendieck sets in the algebra of sets admit a pointwise convergent measure sequence of bounded scalar-valued measures and the measure sequence is weakly convergent in the corresponding Banach space [21]. Thus, a similar question can be asked in the null-extended σ − neighborhood system under finite measures.…”
Section: Topological and Group Algebraic Propertiesmentioning
confidence: 99%
“…It is observed that the Grothendieck sets in the algebra of sets admit a pointwise convergent measure sequence of bounded scalar-valued measures and the measure sequence is weakly convergent in the corresponding Banach space [21]. Thus, a similar question can be asked in the null-extended σ − neighborhood system under finite measures.…”
Section: Topological and Group Algebraic Propertiesmentioning
confidence: 99%
“…In the definition of the Grothendieck set given in [7] (Definition 1) the sentence "each bounded sequence" is replaced by "each sequence". Both definitions of Grothendieck sets agree when B is a Nikodým set for the Banach space ba(A), because then each sequence (µ n , n ∈ N) of ba(A) that B-pointwise converges is B-pointwise bounded, hence it is norm bounded.…”
Section: Strong Grothendieck Setsmentioning
confidence: 99%
“…With the hypothesis of Proposition 3 the next theorem states that M and {χ A : A ∈ M} are strong Rainwater sets for E * and ba(A), respectively. Its argument is based in the proof of [8,Theorem 8].…”
Section: A Hereditary Property Of Rainwater Setsmentioning
confidence: 99%
“…Next lemma is a particular case of [8,Theorem 6], that is based on [7, Proposition 14]. We provide a brief proof for the sake of completeness.…”
Section: Author's Personal Copymentioning
confidence: 99%